Plants of Papi Hill in Andhra Pradesh - Raju, D. C. S. (Indian Forester, 1966)
The Papi hills and the adjoining forest tracts of West Godavari district in Andhra Pradesh have remained botanically unexplored and two seasonal collections were made during the months of March and September, 1962. The vegetation of Papi hill presents a moist deciduous forest with Tectona- Terminaliaxylia association on the red laterite soil at Ravigudem (800 M) A dry deciduous teak and scrub type were also met with on the slopes towards the foot hills bordering, plains. In all a total of 170 species of phanerogams represeting 135 genera and 50 families were recorded. Leguminosae (35 Sp), Euphorbxlceae (9), Rubiaceae (9), Acanthaceae (7), and Gramineae (7), are the five dominant families with their species content of the flora. A few plants like Desmodium laxiflorum DC., Galactia villosa W. and A. and Curcuma decipiens DaJz. Were recorded for the first time on the Eastern Ghats of Northern Circars. New localities were found for Elalosumma cuneolurn Wt., Begonia pieta Sm. And Chlorophylum orchidastrum Lindl. On the southern side of the river Godavari. An enumeration of the species arranged in the order of Bentham and Hooker's classification is given.